The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1001/jamapediatrics.2016.0921
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Infant Protection Against Influenza Illness Conferred by Maternal Immunization

Abstract: Influenza immunization of women during pregnancy protects the young infants against influenza illness. The duration of this protection remains unclear.OBJECTIVE To evaluate the duration of infant protection conferred by maternal immunization and its association with transplacental antibody transfer. DESIGN, SETTING, AND PARTICIPANTSInfants born to women who participated in a randomized, double-blind, placebo-controlled clinical trial in 2011 and 2012 on the safety, immunogenicity, and efficacy of trivalent ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(89 citation statements)
references
References 21 publications
1
86
0
Order By: Relevance
“…The study of Nunes at al 17 demonstrated a similar rapid decay in the first 2 months of life, 12,18 this study 17 provides more conclusive information indicating that there is limited efficacy of maternal influenza vaccination regarding infant protection beyond the second month of life. The investigators suggest that infant protection against influenza in the first few months of life is largely dependent on transplacentally transferred IgG antibodies, relative to breast milk-derived antibodies, as demonstrated by the lack of protection after concentrations of protective serum IgG antibodies have decreased significantly.…”
mentioning
confidence: 59%
“…The study of Nunes at al 17 demonstrated a similar rapid decay in the first 2 months of life, 12,18 this study 17 provides more conclusive information indicating that there is limited efficacy of maternal influenza vaccination regarding infant protection beyond the second month of life. The investigators suggest that infant protection against influenza in the first few months of life is largely dependent on transplacentally transferred IgG antibodies, relative to breast milk-derived antibodies, as demonstrated by the lack of protection after concentrations of protective serum IgG antibodies have decreased significantly.…”
mentioning
confidence: 59%
“…31 A subsequent post-hoc analysis of the South African study reported that whilst vaccine efficacy was 86% (95% CI: 38–98%) in those <8 weeks of age, this declined to 25% (95% CI: -68-68%) and 29% (95% CI: -159-82%) in the 8–16 and 16–24 weeks age-groups, respectively. 32 Although not powered to address vaccine efficacy by narrower age-groups, the observed waning of immunity and efficacy in South Africa was corroborated in the Malian study where vaccine efficacy point estimate also declined from 69% when limited to analysing illness infants <2 months of age, to 33% when including all illness up to 6 months of age. 23 …”
Section: Maternal Influenza Vaccinationmentioning
confidence: 95%
“…Moreover, maternal vaccination was associated with protection of infants from PCR-confirmed influenza illness. But, the protection was short-lived (first 8 weeks of life) and correlated with a decrease in maternally acquired antibodies (6). A longer period of infant protection (4 months) was observed following immunization of pregnant women from Mali during the third trimester of gestation (69).…”
Section: Maternal Immunization To Protect Infants From Neonatal Pamentioning
confidence: 99%
“…Nevertheless, the incidence of other neonatal pathogens such as pertussis has increased over the last 3 decades (4). Importantly, even when infants passively acquire protective levels of pertussis-specific IgG, these antibodies rapidly wane during the first two months of life leaving the infant vulnerable to infection (5, 6). On the other hand, licensed maternal vaccines are not yet available against some life-threatening neonatal pathogens such as group B streptococcus or respiratory syncytial virus.…”
Section: Introductionmentioning
confidence: 99%